Necrotizing Pneumonia – A Rare Complication - Norte, Ana (2012)
Necrotizing pneumonia is a rare complication of community-acquired pneumonia associated with destruction of the lung tissue during the infection and rise of necrotic foci in consolidated areas. Staphylococcus aureus, Streptococcus pyogenes, Nocardia, Klebsiella pneumoniae and Streptococcus pneumoniae are the most common causative agents. Risk factors for developing necrotizing pneumonia include smoking, alcoholism, old age, diabetes mellitus, chronic lung diseases or liver disease. Diagnosis of necrotizing pneumonia requires supportive care, use of broad-spectrum antibiotics and monitoring for sepsis and respiratory failure. Hemoptysis, abscess, empyema and gangrene are possible complications and surgical intervention may be required. The authors present a clinical case of pneumococcal necrotizing pneumonia in a patient without important risk factors and favourable progression with medical therapy. In this regard, a brief bibliographic review about this pathology is also made.